A Kap Study of Hepatitis Among Hepatitis Positive Patients Presenting to a Tertiary Care Hospital in Southern Punjab, Pakistan - Muhammad Mehwar Anjum, Mohammad Hamza Bin Abdul Maik, Muhammad Rizwan, Muhammad Awais Bin Abdul Malik, Rida Saleem, Faiza Khalid, (Pakistan Journal of Medical & Health Sciences, 2022)
Objective: To study prevalence and assessment of knowledge, attitude, and practice regarding hepatitis in patients presenting to a tertiary care hospital in Southern Punjab. Method: The study was conducted at the medicine wards of Sheikh Zayed medical hospital, Rahim Yar Khan for three months from July till September 2021. The data was collected through a physical questionnaire which was divided into three sections relating to prevalence, prevention along with control and risk factors. The collected data was then analysed using SPSS version 26. Results: Out of 219 patients, there were 83 females (38.42%) and 133 males (61.57%). The mean age of the population was found to be 51.74 (15.51). Hepatitis C (86.1%) was found in the highest prevalence. 128 patients (59.2%) were chronic cases while 88 (40.7%) were acute. Regarding co-morbidities, 32.9% patients had diabetes type II (DM-II) and 31.5% of the patients had pre-existing primary hypertension (HTN). In terms of awareness, it was found that 122 (56.5%) attendants/patients were able to correlate their presenting symptoms with hepatitis. 129 (59.7%) of attendants showed some understanding about vaccination. Only the association between the attitude score among males and females was found to be statistically significant (p-value= .003). Conclusion: Despite increasing vaccination trends, hepatitis cases are still prevalent as the most common cause is HCV which has no vaccination. Good prognosis of HCV requires early detection which is rare as the public still lacks knowledge on its disease course and a proactive attitude. Keywords: KAP, Hepatitis C, Pakistan, South Punjab, Hepatitis B, Hepatitis Vaccination, Awareness, Vertical transmission, Hepatitis